(untitled) (Academicia Globe: Inderscience Research, 2023)
This article describes terrorism, in which terrorism changes the worldview of people in order to achieve its goals, seeks opportunities to achieve its objectives based on the effective use of "characteristics" such as fraud, hypocrisy, and selfishness in people’s relationships with people, and is the only way to fight evil., it is analyzed that it is the education of high culture, enlightenment, morals in young people.